MENJEMBATANI KESENJANGAN: Analisis Efektivitas Pelayanan Kesehatan di Puskesmas Bangun Jaya, Daerah Semi-Terpencil - Ramadhanti Musfiroh , Suci; Suratman; Yogopriyatno, Jatmiko (Public Sphere Review, 2024)
This study aims to analyze the Effectiveness of Health Services at Bangun Jaya Health Center. The aspects used to adopt the Theory of Determining Characteristics of Effectiveness Levels, namely availability, accessibility, affordability and acceptability. The research method used is descriptive qualitative, clearly describing the data and facts in the field. Data sources were obtained from secondary and primary data using observation techniques, namely directly observing the object under study and interviews using interview guidelines and documentation by collecting the documents needed. The informants in this study were 9 people using the purposive sampling technique. The results showed a significant medical personnel and equipment shortage at the Puskesmas. This is evidenced by several shortcomings at the Bangun Jaya Health Center, such as the lack of health workers' health equipment and emergency services that are not yet available outside operating hours. This is detrimental to service users because they must look for other health services with the risk of more expensive treatment costs. This is what causes Bangun Jaya Health Center health services not to be optimal enough. In order for this health service to be more optimal, additional medical personnel and equipment upgrades are needed to improve services and add emergency services at the Puskesmas outside of Puskesmas service operating hours.